Simulation of 3D gas–solid fluidized bed reactor hydrodynamics. (2nd January 2017) - Kumar, Umesh; Agarwal, V. K.
ABSTRACT: In this article, an attempt is made to develop a 3D gas–solid fluidized bed reactor (FBR). Basically, it deals with simulation of a FBR in computational fluid dynamics (CFD) using the software, Ansys Fluent v14. The simulation of gas–solid flow is carried out using Eulerian multifluid model which is integrated with the solid particle kinetic theory. The coefficients of exchange momentum are estimated using the Syamlal & O'Brien, Gidaspow, Wen-Yu, and Huilin–Gidaspow drag functions. The results of the simulation have been validated with the experimental data available in literature and had proven that the model is capable to predict the hydrodynamics of FBR. The variation in kinetic energy of the solid phase is calculated by varying the restitution coefficient (RC) from 0.90 to 0.99. The predictions of pressure drop compare excellently with the experimental data. Finally, the effect of particle diameter on the expanded bed height has been studied for FBR.